Research on the Thermal Decomposition Characteristics of PE Outer Sheath of High-Voltage Cables Under Different Humidity Levels - Zhaoguo Wu; Qian Wang; Huixian Huang; Yong Li; Yulai Kuang; Hong Xiang; Junwei Liu; Zhengqin Cao (Energies)
Gas sensors can provide early warning of fires by detecting pyrolysis gas components in the sheaths of high-voltage cables. However, air humidity significantly affects the thermal decomposition gas production characteristics of the outer sheath of high-voltage cables, which in turn affects the accuracy of this warning method. In this paper, the thermal decomposition and gas production characteristics of the polyethylene (PE) outer jacket of high-voltage cables under different air humidities (20–100%) are studied, and the corresponding density functional theory (DFT) simulation calculations are performed using Gaussian 09W software. The results show that with the increase in humidity, the thermal decomposition gas yield of the PE outer jacket of high-voltage cables exhibits a decreasing trend. Under high-humidity conditions (≥68.28%RH), the generation of certain thermal decomposition gases is significantly reduced or even ceases. Meanwhile, the influence of moisture on the thermal decomposition characteristics of PE was analyzed at the micro level through simulation, indicating that the H-free radicals generated by moisture promote the initial decomposition of PE, but the subsequent combination of hydroxyl groups with terminal chain C forms a relatively stable alkoxy structure, increasing the activation energy of the reaction (by up to 44.7 kJ/mol) and thus inhibiting the generation of small-molecule gases. An experimental foundation is laid for the final construction of a fire warning method for high-voltage cables based on the information of thermal decomposition gas of the outer sheath.